Analisis Pengaruh Kualitas Pelayanan, Harga, dan Fasilitas Terhadap Kepuasan Konsumen di Wuling Arista Bekasi - J, Jumawan; Prasetyo, Ade Ilham (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to analyze the impact of service quality, price, and facilities on customer satisfaction at Wuling Arista Bekasi. The automotive industry faces increasing competition, requiring each car dealer to attract customers through various strategies based on their offerings. Consumers generally desire faster and better car buying and selling services. Car dealers, including Wuling Arista Bekasi, must achieve customer satisfaction through various tactics to consistently provide high-quality services. The results of the study indicate that the three variables play an important role in shaping customer satisfaction. Most respondents are satisfied with the quality of service provided, consider the offered prices to be competitive, and appreciate the adequate facilities. However, there is an expectation for more promotions and facility improvements to further enhance customer satisfaction.